The effectiveness of Personal Protective Equipment (PPE) in preventing Covid-19 infection among Healthcare Workers (HCW) – An exploratory study - Mohd Firdaus, Mohd Shaari (2022)
Coronavirus Disease 2019 (Covid-19) has brought occupational health risks to a line of health workers globally. Till date, many hcws have been infected with Covid-19 as a result of exposure while on duty. Various efforts have been taken to prevent contagion or infection from continuing to occur. It is a priority to explore the effectiveness of PPE in preventing Covid-19 infection among healthcare workers. The study aims to listed related issue towards the application of PPE at workplace during Covid-19 pandemic and explain the effectiveness of PPE in preventing Covid-19 infection among healthcare workers. Data for this study was collected through semistructured interviews conducting during data collection process. Covid-19-infected hcws was identified from UKA and those infected due to workplace exposure. The approach in this study is through qualitative approaches. The qualitative approaches were carried out through interviewed with 16 respondents to obtain information and views related to effectiveness of PPE in preventing Covid-19 infection among healthcare workers. Each conversation was voice recorded and each recording was transcribed and analysed manually using coding process. Most of the participants agreed that appropriate PPE is sufficient to prevent infection of Covid-19 among hcws. It is necessary to establish a system that provides a stable supply of PPE for hcws to perform their duties. Most of the participants mentioned that the effectiveness used of PPE was for a short period of time. The use of PPE recommended by MOH and adherence to established sops can lower the risk of infection and increase the effectiveness of PPE used. Recommended checklist observation on provided PPE can be used to evaluate the effectiveness of the PPE provided from time to time, and help the authorities to determine the good selection of PPE to use.